Sekuritisasi National Central Bureau (NCB) Interpol Indonesia dalam Penanganan Buronan Roman Nazarenko - Zsa Zsa Haura Khairunnisa (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
This study examines the securitization process implemented by Indonesia's Interpol National Central Bureau (NCB) in the arrest of Roman Nazarenko, a fugitive identified as the mastermind behind clandestine drug laboratories. Distinct from previous studies that positioned narcotics substances as the primary existential threat, this research demonstrates that an individual—Nazarenko—can represent the core threat due to his transnational capacity to establish illicit drug manufacturing. Employing a qualitative approach with purposive sampling, data were collected through an in-depth interview with a key Interpol official and analyzed using the Miles and Huberman model (data reduction, data display, and conclusion drawing). Applying the Copenhagen School securitization theory, the study finds that NCB Interpol Indonesia's handling of the Roman Nazarenko case encompasses five key elements: securitizing actor, existential threat, referent object, speech act, and audience acceptance. By shifting the referent object of securitization from narcotics substances to the individual, this research elucidates how NCB Interpol Indonesia dynamically securitizes international fugitives. The findings offer fresh insights into operational mechanisms and underscore the vital role of international collaboration in countering transnational organized crime.